The Level of Regional Financial Independence as One of the Benchmarks for Government Performance in Indonesia - Widiastuty, Tri (Accounting Undergraduate (S1) and Diploma Study Program (D3), STIE EKUITAS, 2025)
Introduction/Main Objectives: Indonesia faces global phenomena and also domestic issues that affect commodity prices and ultimately impact the level of regional independence. Background Problems: The independence of each region in Indonesia needs to be supported and the driving factors explored so that each region can develop by relying on the resources available in their respective areas without depending on transfers from the central government. This study aims to examine the influence of balancing funds, local revenue, and economic growth on the level of regional independence. Novelty: This research was analyzed using panel data regression, which differs from previous studies. Research Methods: This research is a quantitative study with a descriptive-verificative approach. Data were analyzed using panel data regression analysis. The population of this study consists of all provinces in Indonesia. The sampling technique used was purposive sampling, resulting in 34 out of 38 provinces with complete data. Finding/Results: The results of this study indicate that balancing funds, local revenue, and economic growth have an impact on the level of regional independence in Indonesia. Conclusion: Higher balancing funds can improve community welfare, thereby increasing the level of regional independence. The increasing local revenue will make the region less dependent on the central government, thereby raising the level of regional independence. If economic growth includes the economy in each region, it can also increase regional income, thereby raising the level of regional independence.